The intrinsic neuronal network of the central nervous system and its modular (subsystem) architecture in a mammal - Larry W. Swanson; Joel D. Hahn; Olaf Sporns (Proceedings of the National Academy of Sciences, 2025)
The vertebrate central nervous system (CNS) has two great topographic divisions—brain and spinal cord—that together integrate the body’s internal physiology and behavioral interactions with the environment. To clarify the architecture of intra-CNS connectivity supporting this integration in a mammal (rat), network science analyses were applied at the level of gray matter regions (nodes) connected by directed and weighted axonal projections. Neuroanatomical evidence indicates a bilateral, predominantly sexually monomorphic neuronal network of 840 nodes and a projected 81,434 direct interconnections (of the 704,760 possible connections), representing a projected network density of 12%; 32% of identified connections terminate contralaterally, and 41% of identified connections participate in bidirectionally linking a pair of nodes. Local network differentiations examined with unsupervised multiresolution consensus cluster analysis revealed a nested hierarchy of interconnected modules (clusters or subsystems) that were conservatively assigned putative functional roles. This structure–function hierarchy includes only three first-order modules, indicating a tripartite systems architecture (distinct from the bipartite brain-spinal cord topographic division): a bilaterally symmetric module pair centered in the forebrain-midbrain, associated with behavior control, cognition, and affect; and a single bilateral module centered in the rhombicbrain-spinal cord, associated with behavior execution and reflex integration. This modular spatial patterning suggests possible developmental and phylogenetic correlates. Additional analyses of the CNS’s basic structural network plan included global neuronal network features—specifically, measures of centrality, rich club, and small world topology—that transcend modular boundaries.